Well-Being Is Associated With Local to Remote Cortical Connectivity - Li, Yubin; Li, Chunlin; Jiang, Lili (Frontiers in Behavioral Neuroscience, 2022)
Well-being refers to cognitive and emotional appraisal of individual’s life and social functioning, which is of great significance to the life quality of an individual and society. Previous studies have revealed the neural basis of well-being, which mostly focused on human brain morphology or network-level connectivity. However, local-to-remote cortical connectivity, which plays a crucial role in defining human brain architecture, has not been investigated in well-being. To examine whether well-being was associated with local-to-remote cortical connectivity, we acquired resting-state images from 60 healthy participants and employed the Mental Health Continuum Short Form to measure well-being including three dimensions: emotional well-being, psychological well-being and social well-being. Functional homogeneity (ReHo) and seed-based functional connectivity were used to evaluate local-to-remote cortical connectivity in these participants. For local connectivity, our results showed that ReHo in the right orbitofrontal sulcus was significantly positively correlated with psychological well-being but negatively correlated with social well-being. For remote connectivity, connectivity within the right orbitofrontal cortex and interhemispheric connectivity of the orbitofrontal sulcus were both positively associated with psychological well-being; functional connectivity between the right orbitofrontal sulcus and the left postcentral sulcus was positively associated with social well-being. Our results showed that well-being was indeed associated with local to remote cortical connectivity, and our findings supplied new perspective of distance-related neural mechanisms of well-being.